2023
DOI: 10.1002/jum.16282
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Feasibility and Diagnostic Performance of ACR CEUS LI‐RADS and a Modified CEUS LI‐RADS for HCC in Examinations Using Sonazoid

Abstract: ObjectivesThe present study aimed to determine the feasibility of the American College of Radiology's (ACR) contrast‐enhanced ultrasound (CEUS) Liver Imaging Reporting and Data System (LI‐RADS) (version 2017) in examinations using Sonazoid and compare its diagnostic performance with that of modified LI‐RADS in patients at high risk of hepatocellular carcinoma (HCC).MethodsThis retrospective study's sample population consisted of 137 participants with a total of 140 nodules who underwent CEUS with Sonazoid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The 26 studies comprised a total of 8,495 patients with 9,244 lesions. Of the studies, 17 used SonoVue ® as the CA ( 13 - 29 ), seven used Sonazoid ® ( 30 - 36 ), and two used both SonoVue ® and Sonazoid ® ( 37 , 38 ). Three studies were prospective ( 13 , 19 , 38 ) and 23 were retrospective ( 14 - 18 , 20 - 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 26 studies comprised a total of 8,495 patients with 9,244 lesions. Of the studies, 17 used SonoVue ® as the CA ( 13 - 29 ), seven used Sonazoid ® ( 30 - 36 ), and two used both SonoVue ® and Sonazoid ® ( 37 , 38 ). Three studies were prospective ( 13 , 19 , 38 ) and 23 were retrospective ( 14 - 18 , 20 - 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were prospective ( 13 , 19 , 38 ) and 23 were retrospective ( 14 - 18 , 20 - 37 ). Of the studies, 10 used histopathology only as the reference standard ( 15 , 16 , 19 , 21 , 23 - 25 , 27 , 30 , 33 ) and 16 used both histopathology and imaging follow-up as the reference standard ( 13 , 14 , 17 , 18 , 20 , 22 , 26 , 28 , 29 , 31 , 32 , 34 - 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The modified algorithm integrates the unique KP characteristics of Sonazoid, but whether it should be more widely applied needs to be confirmed with additional research. Some studies have demonstrated that the two algorithms provide a highly similar diagnostic performance ( 15 , 16 ), while others have indicated that the modified algorithm has superiority in diagnostic sensitivity ( 14 , 17 , 18 ). However, thus far, no meta-analysis comparing the two algorithms of Sonazoid for diagnosing HCC has been conducted.…”
Section: Introductionmentioning
confidence: 99%